The Cisuralian faunal succession in Patagonia (Tepuel-Genoa Basin, Argentina): an update brachiopod biostratigraphic scheme - Pagani, María Alejandra (2011)
The Tepuel-Genoa Basin, located in the Patagonian region (Chubut Province) of southern Argentina, was a wide embayment open to the Panthalassic Ocean at the southwestern border of Gondwana; it was infilled by nearly 7000 m of a continuous succession (Tepuel Group), from the early Carboniferous (late Tournaisian) to the early Permian (Artinskian). Lowermost Permian faunas were recognised in the upper part of the Pampa de Tepuel Formation, but the first record of a Costatumulus-like faunal assemblage starts in the lower part of the overlying Mojón de Hierro Formation and ends in the upper part of the Río Genoa Formation. Recently, refined proposals on the stratigraphic arrangement of the Mojón de Hierro and Río Genoa formations, and discrimination of faunal assemblages throughout these units, allowed us to identify a wide spatial and temporal distribution for Costatumulus Waterhouse within the basin. New material collected from different localities and fossiliferous horizons throughout the Tepuel-Genoa Basin suggests a greater number of species than the previously recorded single occurrence of Costatumulus, and also the presence of its allied genus Magniplicatina Waterhouse. Such adjustment in the taxonomic composition of the former Costatumulus Biozone allows the recognition of six different and successive faunal assemblages; and also three potentially new species of Costatumulus, as follows. The Cimmeriella Fauna (~late Asselian-Sakmarian) recorded with Costatumulus sp. 1 (formerly Cancrinella cf. C. farleyensis), and the Kochiproductus-Costatumulus Fauna (~latest Sakmarian-earliest Artinskian) bearing Costatumulus sp. 2, are both recorded in the upper section of the Mojón de Hierro Formation. The younger Costatumulus-Tivertonia Fauna (~early Artinskian) yields Costatumulus sp. 3 in the lower part of the Río Genoa Formation, whilst the Jakutoproductus (~late early Artinskian), Piatnitzkya (~late early -middle Artinskian) and the youngest Magniplicatina sp. (~middle Artinskian) faunas characterise the uppermost section of the Río Genoa Formation. The taxonomic composition of the Costatumulus Biozone faunal succession in Patagonia initially suggests strong but temporally varied faunal links with western Australia and the Cimmerian regions in south and southeast Asia, as well as moderate but significant links with the Siberian Arctic region and, to a lesser extent, with eastern Australia.